2016
DOI: 10.32890/mjli2016.13.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Gender and Motivational Beliefs on Self-Regulated Learning: A Study at ICT-Integrated Schools

Abstract: Purpose-This study aimed to examine the interaction effects of gender and motivational beliefs on students' self-regulated learning. Specifically, three types of motivational beliefs under the Expectancy-Value Model were examined, namely self-efficacy, control beliefs and anxiety. Methodology-A quantitative correlational research design was used to achieve the research objectives. Data were collected through the questionnaire survey method from 322 secondary school students (166 males; 156 females). The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
5
11
0
Order By: Relevance
“…These results were consistent with a previous study conducted amongst dental students in Croatian universities 8 . In terms of gender, females showed higher satisfaction and a more positive attitude than males towards TB learning, which is similar to the suggestion by other studies that females are more willing to engage in TB learning 24,25 . Nevertheless, other studies have rejected the role of gender in relation to acceptance of or positivity towards TB learning methods 26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with a previous study conducted amongst dental students in Croatian universities 8 . In terms of gender, females showed higher satisfaction and a more positive attitude than males towards TB learning, which is similar to the suggestion by other studies that females are more willing to engage in TB learning 24,25 . Nevertheless, other studies have rejected the role of gender in relation to acceptance of or positivity towards TB learning methods 26,27 .…”
Section: Discussionsupporting
confidence: 92%
“…The study revealed that there were negative relationships between the students' English learning anxiety and their autonomous learning behavior, which confirmed the view that learners' English learning anxiety may hinder their English learning (Yin, Liu, & Ye, 2018;Abdullah, 2016). The results in the present study could be explained by the relationships between the students' mastery goals, learning anxiety, and autonomous English learning behavior as stated above.…”
Section: Relationships Between Learning Anxiety and Autonomous Learnisupporting
confidence: 88%
“…In the global context (Venezuela, Czech Republic, or Malaysia), some authors, such as Rao and Sachs (1999), Jakesöval and Hrbackova (2014), or Abdullah (2016), carried out studies in primary and secondary education populations, looking for knowledge on performance, motivation, and learning strategies. Recently, Angeli dos Santos and Ferreira (2016) analyzed the EMAPRE-U reliability and its validity in Portuguese populations, and Thomas and Muller (2016) used the SMR-L in Austria.…”
Section: Introductionmentioning
confidence: 99%